2020
DOI: 10.1097/jpn.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Land and Water Birth Within the American Association of Birth Centers Perinatal Data Registry, 2012-2017

Abstract: Consumer demand for water birth has grown within an environment of professional controversy. Access to nonpharmacologic pain relief through water immersion is limited within hospital settings across the United States due to concerns over safety. The study is a secondary analysis of prospective observational Perinatal Data Registry (PDR) used by American Association of Birth Center members (AABC PDR). All births occurring between 2012 and 2017 in the community setting (home and birth center) were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 59 publications
0
22
0
2
Order By: Relevance
“…Results are mixed for umbilical cord avulsion in large (>1000 waterbirths) studies. Jacoby et al 39 reported no avulsions in the waterbirth group, and five (0.0002%) in the land birth group, whereas Snapp et al 40 reported 0.5% avulsions in the waterbirth group and 0.3% in the land birth group (RR 1.87, range 1.24-2.82, unadjusted). In a case series of 4030 waterbirths, Gilbert et al 41 reported five infants (0.12%) who experienced umbilical cord avulsion.…”
Section: Interpretationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Results are mixed for umbilical cord avulsion in large (>1000 waterbirths) studies. Jacoby et al 39 reported no avulsions in the waterbirth group, and five (0.0002%) in the land birth group, whereas Snapp et al 40 reported 0.5% avulsions in the waterbirth group and 0.3% in the land birth group (RR 1.87, range 1.24-2.82, unadjusted). In a case series of 4030 waterbirths, Gilbert et al 41 reported five infants (0.12%) who experienced umbilical cord avulsion.…”
Section: Interpretationsmentioning
confidence: 97%
“…Snapp et al 40 found fewer reproductive tract infections (relative risk [RR] 0.73, range 0.52-1.04), and Geissbuehler et al 16 reported less postpartum antibiotic use (3.1% waterbirth, 4.7% land birth), but neither adjusted for confounders. Jacoby et al 39 reported 80% fewer maternal fevers in the waterbirth group than in the land birth group (aOR 0.21, 95% CI 0.03-1.49, adjusted for primiparity). Our own prior work suggested fewer postpartum reproductive tract infections in the waterbirth group (aOR 0.87, 95% CI 0.69-1.09, adjusted for primiparity).…”
Section: Interpretationsmentioning
confidence: 99%
“…The American Association of Birth Centers published results in 2020, from the Perinatal Data Registry, using 5 years of collected data from 2012 to 2017, revealing that 38% (10,252) of cases among 26,684 birth center births took place in the water (Snapp et al, 2020). The findings from this observational study support increasing access to warm water immersion during labor and including water assisted birth.…”
Section: Out Of Hospital Water Birth Optionsmentioning
confidence: 59%
“…None of the groups presented high levels of BMI (24.4±3.7 vs 23.07±3.5, p=0.001) (Table 1), coinciding with studies where the preference for water delivery was higher in women with BMI less than 30 due to complications that can occur in obese women. [35][36][37][38][39][40][41] Regarding neonatal data, the weight of babies at birth was higher in water delivery compared to conventional delivery (3067.4±359.9 vs 3059.7±435.2, p=0.02), in turn, the APGAR in minute 1 did not present significant difference between water and conventional calving (8.9±0.3 vs 9±3.4), unlike APGAR in minute 5 (9.62±0.4 vs 9.5±0.5, p=0.00), which was greater in water calving compared to conventional calving (Table 1); different from that reported, [42][43][44] who report similar APGAR values at minute 1 and 5, between water and conventional delivery.…”
Section: Discussionmentioning
confidence: 99%